Telomere-to-telomere genome assembly of Phoxinus lagowskii - Yanfeng Zhou; Chunhai Chen; Dian Fang; Chenhe Wang; Yajuan Peng; Binhu Wang; Minying Zhang; Yang You; Yixin Liu; Guoping Deng; Jianbo Jian; Dongpo Xu (Scientific Data)
Abstract As an important economic and ecological fish, Amur minnow (Phoxinus lagowskii) plays a significant role in food products as well as evolutionary, ecological research. However, a high-quality chromosome-level genome of P. lagowskii is not currently available. In this study, we report a T2T (Telomere-to-telomere) genome for P. lagowskii with chromosome-level. The finally assembled genome size is 1.04 G, with a contig N50 of 41.7 Mb, comprising 25 chromosomes. The transposable elements constituted 512.40 Mb (49.22%) of the assembled P. lagowskii genome, with DNA transposons 25.02% being the predominant repeat type. A total of 2,4610 protein-coding genes were predicted in P. lagowskii genome, with 99.96% of these genes being functionally annotated. The identification of telomeres, BUSCO assessment, mapping coverage, and sequencing depth collectively demonstrated the high quality of the genome assembly. The T2T genomic information serves as an invaluable resource for studies in evolution, comparative genomics, fish breeding applications, and ecological research.